The impact of digital technologies on vocational education and training needs : an exploratory study in the German food industry - Achtenhagen, Claudia [Verfasser]; Achtenhagen, Leona [Verfasser] (My University, 2019)
"Currently, the hype surrounding digitalization proclaims that the way in which companies create and capture value will change dramatically. Companies that adjust their business models to embrace digital technologies will need different skill sets and competences. Current research tends to focus on the impact of digital technologies on corporations or more generally the labor market, but the authors lack detailed insights into how companies perceive this development to influence their needs regarding employee qualifications. Therefore, the purpose of this paper is to explore how companies perceive the impact of digital technologies on the education and training needs of current and future employees. This study draws on eight case studies from the food industry. It focuses on one occupation certified within the German 'dual system' of vocational education and training (VET), the machine and plant operator with focus on food technology. This study draws attention to the importance of reviewing VET needs in relation to the decision of implementing digital technologies. The empirical study presented in this paper represents preliminary findings connected to a larger project conducted at the Federal Institute for Vocational Education and Training (BIBB) in Germany, in collaboration with the Federal Ministry of Education and Research (BMBF). This paper does not represent a final report of the results." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; G 1.2.3.2 Anforderungen & Bedarfe; G 2.2.1 Technologisierung; G 1.2.4.1.4 Verarbeitendes Gewerbe; S 6.2.8 Maschinisten, Einrichter; T 3 Forschungsmethoden; Berufsausbildung; Duales System; Ausbildungsbedarf; Qualifikationsanforderung; Anforderungsprofil; Technischer Wandel; Digitalisierung; Nahrungs- und Genussmittelgewerbe; Maschinen- und Anlagenführer; Zweijähriger Ausbildungsberuf; Fallstudie; Qualitative Methode